ANALISIS FASILITAS BELAJAR SISWA DI SD MIT FATHRIZK PEKANBARU: Penelitian Deskriptif - Muhammad Oktafiansyah; Guslinda; Muhammad Fendrik (STKIP Subang, 2025)
This qualitative study analyzed the condition of learning facilities at MIT Fathrizk Elementary School, Pekanbaru, through observation, interviews, and documentation. Results showed that most facilities, such as classrooms, the library, and the sports area, were adequate, with good lighting and ventilation. However, limitations were found in digital teaching aids, the school's health and safety room being integrated with the administration, and the less-than-ideal toilet ratio. Good facilities have been shown to increase learning motivation, while deficiencies hinder learning effectiveness. It was concluded that the school needs to improve learning technology and the quality of supporting facilities. Recommendations include the development of learning media and regular evaluation of facilities.